UMS nursing student awareness on the impact of social media on nursing profession - Patricia Sator; Jummaiyah Md Tahir; Elvinna Maria Joannes; Nafisah Mokti (Malaysian Journal of Medicine and Health Sciences, 2020)
Social media have been used widely by majority of population around the world and have been proved to be useful for sharing information as well as gain knowledge. For student, media social plays a huge role especially during learning session. Recently, a lot of issues regarding nursing services flooded social media, which gave a negative impression about nurses profession. This study aims to identify the awareness on the impact of social media in regards to nursing services among Faculty of Medicine and Health Sciences (FMHS), UMS nursing students. Methods: Descriptive quantitative cross-sectional study using modified questionnaire for data collection was conducted in FMHS, UMS. A total of 100 nursing student, year 3 (37%), year 2 (40%) and year 1 (23%) participated in the study. Results: Overall, 51% respondents agree and 45% strongly agree that social media is a powerful tool to connect among individuals. 63% agree and 34% strongly agree that social media can make jobs more efficient and innovative. 63% agree and 32% strongly agree that social media can be an agent of providing clinical education to nurses by facilitating conversations with colleagues about best practice and advanced healthcare. 51% agree and 22% strongly that social media can be trace and legal action can be taken towards nurses. 54% agree and 20% strongly agree that social media can be used to reveal malpractice among nurses. 45% agree and 40% strongly agree that social media can be misuse by the non-healthcare provider. Conclusion: Based on this study’s result, the respondents are well aware with the positive and negative impact of social media on nursing profession. There may has a small number of unaware or unsure about the impact among the respondents, with that the recommendation for this study is to ensure the UMS nursing students to abide with the professional and personal etiquettes and use common sense and caution while communicating on social media.